The Alteration and Clinical Significance of Th22/Th17/Th1 Cells in Patients with Chronic Myeloid Leukemia - Ping Chen; Min Wang; Daqi Li; Yan Jia; Na He; Wei Li; Daoxin Ma; Chunyan Ji (Journal of Immunology Research)
T helper- (Th-) cell immunodeficiency plays important roles in tumor development and their effects in chronic myeloid leukemia (CML) remain unclear. In the present study, we mainly investigated the role of Th22, Th17, and Th1 cell and their related cytokines (IL-22, IL-17, and IFN-r) in the pathophysiology of CML. Bone marrow (BM) and peripheral blood (PB) were extracted from newly diagnosed (ND), chronic phase- (CP-) CML patients, and controls. Th subsets were examined by flow cytometry. Plasma IL-22, IL-17, and IFN-r concentrations were measured by ELISA. AHR and RORC mRNA expressions were examined by RT-PCR. The frequencies of Th22, Th17, and Th1 cells, along with the expression of specific transcription factors RORC and AHR, were significantly decreased in ND patients compared with healthy controls, while all these abnormality recovered in CP patients. In addition, there existed a significantly positive relationship between Th22 and Th17 cells in PB or BM. A significantly negative relationship was found between Th cells (Th22, Th17, or Th1) and BCR-ABL (%) IS or the number of PB white blood cells. All these results demonstrated that Th22, Th17, and Th1 cells might be important therapeutic targets in CML and could facilitate a better outcome for tumor immunotherapy.